Factor Influencing Farmers’ Decisions in Marketing Rice Harvests in Megang Sakti II, Musi Rawas Regency, South Sumatera - sulastri, merna ayu; Setiawan, Trio; Sari, Dwi Wulan; Huanza, M (Sriwijaya Journal of Agribusiness and Biometrics in Agriculture Research, 2024)
Indonesia is known as an agricultural country that prioritizes the agrarian sector with the majority of the Indonesian population working as farmers. Musi Rawas Regency is a producer of food commodities and has a large contribution to the agricultural sector in South Sumatra. This research aims to analyze the mechanism of selling rice harvests, to compare the sales and consumption of rice harvests, and to analyze the factors influencing farmers' decisions to sell rice harvests in Musi Rawas Regency, South Sumatra. The study was conducted in Megang Sakti II Village with rice farmer respondents who met specified criteria, using interview and questionnaire methods, and sample selection through purposive sampling technique. The results indicate that the mechanism for selling rice harvests is in the form of dried milled rice, with a milling payment system deducting 10% from the total rice, and the entire sales are marketed to middlemen. The average sale of rice harvests is 77.48%, with a consumption percentage of 22.52%. The independent variables that significantly influence farmers' decisions to market rice harvests in Megang Sakti II Village are production result with a value of 0,040 and household income with a value of 0,025. Keywords: factor, marketing mechanism, and rice harvest